The Language of Innovation: Promoting STEM Literacy and Computational Thinking in the Digital Age - Mafarja, Nofouz; Mohamad, Mimi Mohaffyza; Zulnaidi, Hutkemri; Mohd Affandi, Haryanti (Journal of Technical Education and Training, 2025)
In the digital age, fostering STEM literacy and computational thinking skills is crucial for individuals to succeed in a technology-driven society. This research aims to assess STEM literacy and computational thinking among students in Malaysia’s public universities. A quantitative survey was conducted involving 200 students in STEM fields. The study found a strong correlation between STEM literacy and computational thinking skills among students with a moderate level of literacy and thinking. However, there was no difference in the innovative teaching methods used in the classroom. The findings suggest integrating innovative language into STEM education and outreach initiatives can enhance STEM literacy and computational thinking skills. The study’s implications extend to educators, policymakers, and stakeholders seeking to develop effective strategies for promoting STEM literacy and computational thinking in the digital age. This will equip individuals with the essential skills needed to succeed in a technology-driven world. However, the findings not only have implications for STEM educators or practitioners but also for TVET educators. TVET programs need to incorporate STEM literacy and computational thinking into their curricula.